SCHOLARS' VIEWS ON MIGRATION MANAGEMENT AND THE EFFECTS OF MIGRATION ON THE SOCIOECONOMIC LIFE OF TÜRKİYE (Third Sector Social Economic Review, 2023)
This study has been prepared to discuss the causes of migration and its effects in the host country, how this effect is perceived and evaluated by the society, the level of effectiveness of the policies developed by the administration, and finally the future projection of migration from the academic perspectives of scholars. The research question of which direction the severity and course of the socioeconomic impact of the refugees in the host country develop in the process is determined for this investigation. The study group of this research consists of two Professors, three Assoc Professors, and two Assistant Professors, totaling seven scholars. The inquiry was carried out using the phenomenology or philosophy of experience methodology, one of the popular qualitative research procedures. For the data collection process, a semi-structured interview form was used, and the obtained data were analyzed by descriptive analysis technique. As a result of this research, three main themes of forced migration and its effects, policies for forced migration, and future projections were formed. Under the theme of forced migration and its effects, sub-themes of refugee identity, source of motivation, demography and poverty, opportunity and threat, population density and hospitality, and distribution of wealth are included. Under the theme of policies for forced migration, the sub-theme of legal status, legal framework, and fundamental rights are included. Under the theme of future projection, the sub-themes of socioeconomic instability, level of development, and voluntary return of the temporarily protected are included. After this research was conducted, it was concluded that the current legal legislation associated with the refugees under the phenomenon of temporary protection status situation, causes them to be perceived as permanent guests, which in turn has a negative impact on their integration and adaptation processes into the local societies that they live in. In addition, it was emphasized that migration will continue in the near future, and there is a need for more concrete policies for education, accommodation, employment, and the integration process of refugees based on the permanence thesis.
Keywords: Migration; Migration Management; Refugee; Social Problem; Social Policy